2016
DOI: 10.1021/acsnano.5b06110
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Effects in the Nonlinear Response of Graphene Plasmons

Abstract: The ability of graphene to support long-lived, electrically tunable plasmons that interact strongly with light, combined with its highly nonlinear optical response, has generated great expectations for application of the atomically-thin material to nanophotonic devices. These expectations are mainly reinforced by classical analyses performed using the response derived from extended graphene, neglecting finite-size and nonlocal effects that become important when the carbon layer is structured on the nanometer s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
126
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(129 citation statements)
references
References 70 publications
1
126
0
Order By: Relevance
“…Thus, in this paper we only consider the third-harmonic generation, namely m = 3 and the conductivity tensor is described by a single scalar function. This function can be written as [10][11][12]:…”
Section: Linear and Nonlinear Optical Properties Of Graphenementioning
confidence: 99%
“…Thus, in this paper we only consider the third-harmonic generation, namely m = 3 and the conductivity tensor is described by a single scalar function. This function can be written as [10][11][12]:…”
Section: Linear and Nonlinear Optical Properties Of Graphenementioning
confidence: 99%
“…There are a number of theoretical papers discussing the effect of plamonics on graphene's nonlinearity [122,126,[132][133][134]. Pertaining to waveguide structures, as early as 2010, Skryabin et al [131] derived a set of expressions from the nonlinear Schrödinger equations (NLSEs) to describe the surface effects of various subwavelength plasmonic waveguide structures and coined the term SINE.…”
Section: (B) Surface-induced Nonlinear Enhancement In Graphene Plasmomentioning
confidence: 99%
“…It was found that, due to its highly resonant structure, the TPA process could be switched on or off depending on the Fermi level of the graphene dot. In later works, Cox and co-workers also studied triangularshaped graphene nanoislands [133,143] and found that the nonlinear response varies with the size, Fermi level as well as the edge structures (armchair or zigzag) of graphene, as shown in figure 16. You et al [144] studied the nonlinear enhancement of graphene ribbons and discs on the third-harmonic generation efficiency.…”
Section: (B) Enhancement Of Nonlinearities Through Graphene Nanostrucmentioning
confidence: 99%
“…Additionally, the anharmonic electron motion associated with the Dirac cones of this material [42,43] gives rise to an extraordinary nonlinear response in extended samples [44][45][46]. LSPs in graphene nanoislands have been predicted to produce unprecedentedly high harmonic generation and wave mixing [47,48], indicating their strong capability for nonlinear optical sensing.In this Letter, we show through atomistic quantummechanical simulations that both the linear and nonlinear optical response of graphene nanoislands can be dramatically altered by the presence of a single neighboring molecule that carries either an elementary charge or a permanent dipole of only a few Debye. As a proofof-principle demonstration, we focus on small graphene nanohexagons (GNHs), similar to those produced with high quality through chemical synthesis [49,50].…”
mentioning
confidence: 99%
“…Additionally, the anharmonic electron motion associated with the Dirac cones of this material [42,43] gives rise to an extraordinary nonlinear response in extended samples [44][45][46]. LSPs in graphene nanoislands have been predicted to produce unprecedentedly high harmonic generation and wave mixing [47,48], indicating their strong capability for nonlinear optical sensing.…”
mentioning
confidence: 99%